Going back to the roots of socioemotional wealth. (21st November 2016) - Cruz, Cristina; Arredondo, Horacio
Abstract : Purpose: This commentary elaborates further upon the work by Martin and Gomez-Mejia (this issue) about the two-way relationship between financial wealth and socioemotional wealth (SEW). This paper aims to provide a better understanding of the micro-foundations of the SEW approach, and how the research community could further develop it based on the SEW behavioral roots. Design/methodology/approach: The paper explores recent refinements of the SEW approach, its underpinnings, limitations and potential. It undertook a review of the behavioral foundations of SEW, exploring the implications of those foundations in the interplay between SEW and financial wealth. It also examines aspects of SEW that are still under researched using behavioral lens, as well as some ideas about how the field could move forward. Findings: The authors note that the SEW approach has become so widespread that some are wrongly using it just as an "umbrella term" to account for the non-economic utilities of family owners, forgoing its theoretical roots and implications. Drawing on its theoretical foundations, the authors theorize on the limitations of the SEW approach when wrongly used, and on its potential when properly applied. The main conclusion is that if the SEW approach aims at becoming a dominant paradigm in the family business field, then going back to its behavioral foundations is needed. Research limitations/implications: The main conclusion is that if the SEW approach aims at becoming a dominant paradigm in the family business field, then going back to its behavioral foundations is needed. Originality/value: Overall, this work calls for the use of a "back-to-the-basics" strategy, in which the field clearly understands the original purpose of the SEW perspective, as well as its limitations and potential to become a dominant paradigm in the family business field.